Comparison of Performance of Packet Scheduling Algorithms in LTE-A HetNets - Al Kim, Haider Abdul Hassan Hadi; Subramanian, Ramprasad; Afroz, Farhana; Sandrasegaran, Kumbesan (Wireless personal communications, 2017)
The concept of usage of heterogeneous networks ( HetNets) is about improving the LTE system performance by increasing the capacity and coverage of the Macro cell. In this paper, a performance comparison of various packet scheduling algorithms such as Proportional Fair, Maximum Largest Weighted Delay First and Exponential/Proportional Fair is studied in detail in the HetNets environment. The key performance indicators such as throughput, packet loss ratio, delay and fairness are considered to judge the performance of the scheduling algorithms. Various strategies such as increasing the number of Pico cells in the cell edge were used in the simulation for the performance evaluation study. The results achieved through various simulations show that adding Pico cells to the existing Macros enhances the overall system performance in addition to the various scheduling algorithms implemented in Macros. For reader’s convenience, various types of graphs have been used to represent the simulation results to better understand the performance metrics of various scheduling algorithms. Simulation results shows that overall system gain has increased because of adding Picos and thereby providing better coverage in the cell edge areas and thereby increasing the capacity of the network to provide better quality of service.